Vue sur le patrimoine privé de l’empereur dans une province procuratorienne. - Zheira Kasdi (Antiquités Africaines)
The large imperial estates in Mauretania Caesariensis are evidenced by a series of inscriptions that have never been the subject of a comprehensive study. The limited quantity of this documentation, along with its fragmentary and sometimes enigmatic nature, may have posed an obstacle to the study of these territories. This article aims to provide a general overview of these estates in two stages. Based on the available sources explicitly related to the imperial saltus, the first objective is to locate the properties in Caesariensis. The second objective is to attempt to assess the influence of the competent authorities over these territories, namely the financial procurator and the gubernatorial procurator.